Information Management for Multi-Agent Systems - Alhamwy, Yasin (Electronic Communications of the EASST, 2021)
Multi-Agent Systems (MAS) are becoming increasingly popular in large-scale dynamic domains such as Smart Cities and Search & Rescue (S&R) missions. In order for agents to cooperate efficiently in such domains, they need to distribute tasks, share knowledge, resolve conflicts, incorporate unknown agents, assign roles among each other, assign and keep track of teams of agents, etc. The cooperation in such dynamic domains requires both a software platform that supports the interoperability of cyber-physical agents as well as a shared Knowledge Base that stores general semantic information about the entities of discourse as well as live status information. ALICA, which is an in-house Multi-Agent platform, addresses such domains and is well suited to tackle a lot of these problems. To further enhance its capabilities, an extension is planned in order to integrate the standardised context information interface NGSI-LD as well as the widely used FIWARE models and components for Smart Cities, which enables the management of static and dynamic context information in normal and crisis situations.